Feasibility Analysis of FTTH Network Design with Link Budget and Rise Time Budget Methods - Maria Ulfah; Andi Sri Irtawaty (Poltanesa, 2025)
This research is about the design of FFTH network with GPON technology in Nirmala Residence housing in Balikpapan. The activities of housing residents who in the future will do a lot of digital services such as triple play (voice, data, video), a reliable internet network is needed. It is necessary to develop a Fiber to The Home (FTTH) network as an ICT facility that has high reliability because it uses fiber optic cable transmission media. In FTTH design it is necessary determining the location of ODC and ODP and feasibility analysis through link power budget calculation, rise time budget. This design uses 1 ODC and 6 ODPs spread across the cluster area. The calculation of the total loss value meets the eligibility standard of <28 dB in both the uplink and downlink directions of 21.957 dB and 22.1556 dB. The results of the link power budget calculation for uplink and downlink are -16,957 dBm dBm and  -17.1556 dBm. The rise time values for upstream and downstream are 0133672 ns and 0.29 ns. The results of this calculation meet the required values so that the network design can be implemented.